THE LAND WORKS IN THE KABARDIN-BALKARIAN AUTONOMOUS REGION IN 1922-1928: PREPARATION, IMPLEMENTATION, INTERACTION OF AUTHORITIES - A. H. ABAZOV; A. Zh. SHEREUZHEV (Кавказология)
The article examines the peculiarities of conducting land management work in the Kabardino-Balkarian Autonomous Region in 1922–1928. The reasons are considered and the stages of their implementation are distinguished, the features of their preparation and implementation in the Nalсhiс, Baksan, Urvan and Malokabardinsky districts of the KBAR are determined. Migration, stratification and financial aspects of land management were studied. Particular attention is paid to the activities of the Land Administration of the KBAR – the executive body responsible for the preparation and implementation of land management work in the region. The activity of rural executive committees to carry out land management work in the territory under their jurisdiction was analyzed. The amount of financing required for land management in KBAR has been determined. The peculiarities of cooperation between regional and central government bodies on this issue were revealed. The position of the Soviet government on the provision of a loan to the KBAR for these events is described. The number of people who moved to new places as part of land management work has been established. The names of the settlements formed in the KBAR after resettlement are given. It is concluded that one of the main goals of land management in the KBAR in the 1922–1928 century was a uniform distribution of the population on the flat and foothill parts of the region, rational use of the land fund and opposition to social stratification in the peasant environment.